Globally Monotonic Tracking Control of Multivariable Systems - Ntogramatzidis, Lorenzo; Tregouet, J.; Schmid, R.; Ferrante, A. (Institute of Electrical and Electronics Engineers, 2016)
© 1963-2012 IEEE. In this technical note we present a method for designing a linear time invariant (LTI) state-feedback controller to monotonically track a step reference at any desired rate of convergence for any initial condition. This method is developed for multi-input multi-output (MIMO) systems, and can be applied to strictly/nonstrictly proper systems, and also minimum/nonminimum-phase systems. This framework shows that for MIMO systems the objectives of achieving a rapid settling time, while at the same time avoiding overshoot/undershoot, are not always competing objectives.